Evaluation of Frequency Support using Synthetic Inertia for GFM Inverters - et. al., Shanmugapreethi V, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Grid-following(GFL) PV inverter cannot control the voltage and frequency of the grid. With the high penetration of renewable resources into the grid, the inertia of the system was reduced drastically. This leads to frequency stability problems especially when there is excessive power generated. This study represents the ability to increase the frequency using virtual inertia. Implementation of virtual inertia could damp out all the frequency oscillations and improves the grid stability. The inverters which can control the voltage and the frequency of the grid are known as the grid-forming(GFM) inverters. GFM inverters help in damping the frequency oscillations while the GFM inverters increase the problems related to frequency stability. To exploit the innate damping of GFM inverters energy reserves are critical. Implementation of the virtual inertial in renewable machine controls could increase the power quality. The network has been simulated in PSS®E from which the respective dynamic studies results have been obtained.